Recent Advances in Bone Tissue Engineering: Enhancing the Potential of Mesenchymal Stem Cells for Regenerative Therapies - Milena Kostadinova; Miryana Raykovska; Radoil Simeonov; Stephan Lolov; Milena Mourdjeva (Current Issues in Molecular Biology)
Bone tissue engineering (BTE) has emerged as a promising strategy for addressing bone defects and disorders that cannot be repaired through traditional methods. This field leverages the potential of various biomaterials, cells, and bioactive factors to promote bone regeneration. Mesenchymal stem cells (MSCs) have gained significant attention due to their osteogenic potential, which can be enhanced through osteoinductive factors. Osteoinductive factors, including growth factors like BMPs, TGF-β, VEGF, and IGF, play a crucial role in stimulating the osteodifferentiation process, thereby promoting bone regeneration. Furthermore, bioprinting technologies have opened new avenues for precisely designing scaffolds that can mimic the native bone architecture and provide a conducive environment for MSC differentiation. The integration of bioprinting with mesenchymal stem cells and osteoinductive factors has the potential to revolutionize regenerative therapies by allowing for the creation of patient-specific bone grafts. This review highlights the latest developments in MSC-based therapies, the role of osteoinductive factors, and the impact of bioprinting in advancing BTE. It also discusses future directions for improving the efficacy and clinical translation of these technologies.